Validation of the Maher Multidimensional Talent Assessment Scale (MMTA) for Secondary School Students - Saadati Shamir, Abutaleb; Khorvash, Bita (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to validate the Maher Multidimensional Talent Assessment (MMTA) self-report scale for male and female students in the first stage of secondary education.Methodology: This study employed a descriptive design and was quantitative in nature, categorized as a psychometric research study. It was applied in terms of purpose and utilized a survey method for data collection. From a methodological perspective, it was an assessment tool development study that incorporated correlation methods, goodness-of-fit studies, factor analysis, reliability analysis, and the extraction of standardized scores to examine the degree of correlation and alignment between questionnaire variables and theoretical foundations, as well as to standardize the questionnaire. The statistical population included all students aged 10 to 12 years in the first stage of secondary education from public and non-profit schools in District 1 of the Tehran Department of Education. From this population, a total of 200 female and 200 male students participated in the study. Data analysis methods included Pearson correlation, exploratory and confirmatory factor analysis, Cronbach’s alpha analysis, and standard score calculations.Findings: Findings from exploratory factor analysis, conducted using principal component analysis with Varimax rotation on the 52 items of the MMTA scale, identified five distinct factors. Based on the results of standardized path coefficients, the first factor, "Abilities and Skills," included 12 items with a path coefficient of 0.65. The second factor, "Valuable Goals," consisted of 10 items. The third factor, "Personal Capabilities," comprised 10 items with a path coefficient of 0.36. The fourth factor, "Interest and Enthusiasm," included 8 items with a path coefficient of 0.35. The fifth factor, "Preferred Professions," consisted of 12 items with a path coefficient of 0.58. These findings were statistically significant at the 0.005 level (P < 0.005). The reliability results for the MMTA scale for male and female secondary school students showed that the Cronbach’s alpha coefficient for the overall scale was 0.92. The Cronbach’s alpha values for the subscales were as follows: 0.91 for abilities and skills, 0.89 for valuable goals, 0.93 for personal capabilities, 0.88 for interest and enthusiasm, and 0.89 for preferred professions. Additionally, test-retest correlation coefficients for the overall test were 0.79.Conclusion: The findings indicate that the MMTA scale, with its five components, is a suitable tool for assessing students' talents.